R&D investment and total factor productivity in China’s pharmaceutical industry: The moderating effect of the centralized procurement policy - Xiujuan Li; Jiachun Xu (PLoS ONE, 2025)
We use the implementation of China’s centralized procurement policy as a quasi-natural experiment to examine the effects of China’s centralized procurement policy on pharmaceutical research and development (R&D) investment and total factor productivity (TFP). Empirical findings demonstrate that the positive impact of R&D investment on TFP has a delayed effect in the pharmaceutical sector. The centralized procurement policy shortens this lagged effect by imposing survival pressure and pushing companies to enhance their R&D investment intensity significantly. From the heterogeneity perspective, for companies facing significant financing constraints, the centralized procurement policy significantly enhances the intensity of R&D investment. In contrast, for companies with weaker finance limitations, the impact of the policy on their R&D investment intensity is insignificant. Still, the positive moderating effect of the policy on the relationship between R&D investment and TFP is more pronounced. Based on the findings, policymakers need to take a long-term view and consider the diversified influence of different enterprises. Policies that reduce financing constraints and create an enabling environment for sustained R&D are important and complementary.